The fruits of landscape: the power of landscape in presenting sustainable food production - Mann, William T. (Kansas State University, 2013)
Our current agricultural system in the U.S. involves procedures that appear to maintain high levels of productivity. However, the long-term outlook regarding this system indicates an overall degradation of the ecological resources that generate the abundance of agricultural products to which we are accustomed (Lyle, 1994). This project applies sustainable food production strategies specifically addressed in permaculture as a regenerative alternative to industrial agriculture to a site on the Kansas State University campus. This research initiative quantifies the productive benefits of sustainable agriculture in providing for the Derby Dining Hall, and illustrates how sustainable food production strategies can be shaped through landscape form and space in ways that connect people with ecologically sound food production. The literature review addressed landscape architecture theory and sustainable agriculture. In addition, a set of interviews as well as three precedent studies helped to focus project considerations and to inform design decision-making. The site design process comprised the primary method for exploration and subsequent development of conclusions. The first two design iterations were performed with a specific focus on garden productivity and then garden form, with the third acting as a synthesis of the first two. The final plan suggests that there is a potential for a positive didactic experience of sustainable food production through the artful synthesis of landscape form, particularly with regard to carefully arranged circulation patterns. In addition it was found that, given the average growing season rainfall of 3 inches per month, the water harvested from the roofs of Moore and West residence halls can support over 7,300 square feet of intensive produce beds with a 1 inch per week application rate. In regard to food production, select non-bulk items on Derby Dining Hall’s menu (e.g. Parsley, Garlic, Basil, Kale, Radishes, Turnips, & Oregano) can be provided for or supplemented entirely, given the designed array of produce in the proposed gardens. It would appear that incorporating permaculture and organic farming strategies into the campus fabric would facilitate K-State Housing and Dining’s efforts to promote healthy food -- and sustainable thinking -- by increasing the variety, freshness and interest of its menu.
Keywords: Sustainable food production; Permaculture; Agriculture; Landscape form; Regenerative; Landscape Architecture (0390)